Seasonal distribution and removal efficiency of microplastics in landfill leachate treatment plants in Istanbul, Turkiye - Kara, Narin; Erkan, Hanife Sari (ELSEVIER, 2025)
Due to inadequate management, plastic waste accumulates in landfills and transforms into microplastics (MPs), which concentrate in leachate and pose risks to ecosystems and human health. This study examines the seasonal variation, size, type, and removability of MPs in leachate from the K & ouml;m & uuml;rc & uuml;oda (LTP-1) and Odayeri (LTP-2) landfill leachate treatment plants in Istanbul. Seasonal samples from raw leachate (RL), membrane bioreactor (MBR), ultrafiltration (UF), nanofiltration (NF), and nanofiltration concentrate (NFC) units were analyzed in spring and autumn. The highest MP concentrations were found in MBR units, with 29 particles/L in autumn and 11 particles/L in spring at LTP-1. In LTP-2, MP concentrations in anoxic and aerobic units were 20 and 24 particles/L in autumn and 17 and 26 particles/L in spring. Significant MP reduction was observed in UF and NF outlets, with an MP removal efficiency of approximately 97 % between RL and NF units at both sites. The predominant MPs were blue, black, and transparent fibers, ranging from 500 to 1999 mu m in autumn and 1000 to >2000 mu m in spring. Polymeric analysis identified polyamide (PA) as the most prevalent material at LTP-1 (42 %), followed by polypropylene (PP) and polyisoprene (PI), while at LTP-2, PP was dominant (46 %), followed by polyethylene (PE), PI, and PA. Despite high removal efficiencies, daily MP release after treatment was estimated at 5 x 10(5) and 13 x 10(5) particles for LTP-1 and LTP-2, respectively, indicating continued MP discharge. The high number of MPs detected in untreated landfill leachate, along with their persistence even after treatment processes, highlights the potential accumulation and toxicity risks posed by MPs released into aquatic ecosystems. Further research should focus on understanding the long-term environmental behaviour of these pollutants in receiving environments, as well as on improving advanced treatment technologies for MP removal.
Keywords: Microplastic; Landfill leachate; Leachate treatment plant; Seasonal distribution; Microplastic removal; WATER TREATMENT PLANTS; POLLUTION; RIVER; IDENTIFICATION; ENVIRONMENTS; TRANSPORT; Engineering